Mechanisms of action and processes of yoga-based group intervention for inpatients with schizophrenia spectrum disorders–A longitudinal qualitative study - Töbelmann, Laura; Hahne, Inge; Schulze, Theresa; Bergmann, Niklas; Fuchs, Lukas; Zierhut, Marco; Hahn, Eric; Böge, Kerem (Frontiers in Psychiatry, 2023)
Research exploring the effects of yoga therapy (YT) on individuals with schizophrenia spectrum disorders (SSD) is scarce. Therefore, the current study aimed to explore possible mechanisms of actions and processes, as well as adverse effects of a novel yoga-based group intervention (YoGI) for in-patients with SSD in a German university hospital setting. A longitudinal qualitative study was integrated into a rater-blinded randomized controlled trial, exploring the impact of a four-week YoGI as add-on treatment. In-depth interviews were conducted with participants receiving YoGI (n = 19) in addition to treatment as usual (TAU) and a control group (n = 14) which only received TAU. Interviews were conducted at baseline (n = 33) and four weeks post-intervention (N=28) to assess the participant’s experiences and how they changed over time. The interviews (N=61) were audio-taped, translated, coded, and analyzed by means of inductive thematic analysis. Separate case summaries were prepared for each participant to analyze longitudinal changes within subjects. The research team members collaboratively discussed the final list of themes and subcodes. Rater-based questionnaires, such as the Positive and Negative Syndrome Scale (PANSS), Calgary Depression Scale for Schizophrenia (CDSS) and Personal and Social Performance Scale (PSP) were administered at baseline to assess clinical outcomes. At baseline, participants reported a desire to improve their stress- and symptom management. A minority of participants expressed reservations towards yoga, and several psychosocial barriers were named, including worries about symptom exacerbation. At post- intervention, four mechanisms of change became evident from the interviews: 1) acquiring competence in relaxation, 2) increased interoceptive awareness, 3) feeling connected, and 4) a sense of spiritual well-being. A small number of participants reported difficulties with YoGI. Generally, YoGI positively influenced participants' experiences of their inpatient stay, regarding distress, self- and body awareness, social connectedness, and spiritual well-being. However, participants also illuminated necessary adjustments to improve the intervention. YoGI will therefore be adapted and further developed in an iterative process based on a participant involvement approach. The efficacy regarding outcomes and processes needs to be investigated in a future larger-scaled randomized controlled trial.